Quizizz application training as an alternative to learning assessment - Ernawati; Shinta Wahjusaputri; Hari Setiadi; Firmansyah; Rini Yaumi Habibah; Syarifah, Nur (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2023)
ABSTRACT In this new normal era, academics, especially teachers, are required to continue to look for various learning media so that the learning process can continue both face-to-face at school or online. Teachers are also continuously required to develop competencies both in the personal, social, and professional pedagogical realms. Of the four main competencies, there are two core competencies related to the use of technology and information. To develop these abilities, teachers feel the need to study the latest learning media so they can continue to innovate in the learning and assessing process. Competency development in the use of this technology is one of the problems experienced by SDT Pelita Hati. Therefore, to assist teachers in increasing competence in the use of information technology at SDT Pelita, the UHAMKA Community Partnership Program will conduct online assessment media training. Current learning media used during the learning and assessment process can use gamification-based learning media. One of the popular gamification-based learning media is the Quizizz application. Related to this application, PKM SPS UHAMKA held an activity with the topic